Grace and Agency in Paul and Second Temple Judaism: interpreting the transformation of the heart - Wells, Kyle B. (Supplements to Novum Testamentum, 2015)
Preliminary Material /Kyle B. Wells -- 1 Introduction /Kyle B. Wells -- 2 Deuteronomy 30: God and Israel in the Drama of Restoration /Kyle B. Wells -- 3 Heart Transformation in the Prophets: Jeremiah and Ezekiel /Kyle B. Wells -- 4 The Septuagint /Kyle B. Wells -- 5 The Dead Sea Scrolls /Kyle B. Wells -- 6 The Apocrypha and Pseudepigrapha /Kyle B. Wells -- 7 Philo /Kyle B. Wells -- 8 Paul’s Reading of Deuteronomy 30 in Romans 2:17–29 /Kyle B. Wells -- 9 Paul’s Reading of Restoration: Further Considerations /Kyle B. Wells -- 10 Paul’s Reading of Restoration Outside Romans /Kyle B. Wells -- 11 Conclusions /Kyle B. Wells -- Bibliography /Kyle B. Wells -- Index of Ancient Literature /Kyle B. Wells -- Index of Names /Kyle B. Wells -- Select Index of Subjects /Kyle B. Wells.